A companion to American military history - Bradford, James C. (Chichester, U.K. ; Malden, MA : Wiley-Blackwell Pub., 2010)
'Through more than 60 scholarly essays, A Companion to American Military History presents a comprehensive analysis of the historiography of United States military events and experiences from the colonial era to the present. Including contributions from both eminent military historians and emerging scholars, the essays address every American war from the Indian and imperial conflicts of the seventeenth century to the current battles in Afghanistan and Iraq. All branches of the armed services are covered, including the Continental and Confederate States of America armies, navies, and marine corps, the Coast Guard, militia, National Guard, and reserve forces'--Page 2 of cover.
v. 1. Wars; the armed forces -- v. 2. Foreign military operations short of declared war; homeland security; military specialties; the military; American society and culture.
Includes bibliographical references and index.
Print version record.
Keywords: HISTORY -- Military; Militär.; United States -- History, Military; United States; USA; Electronic books; Military history